1994
DOI: 10.1182/blood.v84.11.3948.bloodjournal84113948
|View full text |Cite
|
Sign up to set email alerts
|

Successful engraftment of T-cell-depleted haploidentical "three-loci" incompatible transplants in leukemia patients by addition of recombinant human granulocyte colony-stimulating factor-mobilized peripheral blood progenitor cells to bone marrow inoculum

Abstract: Patients who undergo transplantation with haploidentical “three-loci” mismatched T-cell-depleted bone marrow (BM) are at high risk for graft failure. To overcome the host-versus-graft barrier, we increased the size of the graft inoculum, which has been shown to be a major factor in controlling both immune rejection and stem cell competition in murine models. Seventeen patients (mean age, 23.2 years; range, 6 to 51 years) with end-stage chemoresistant leukemia were received transplants of a combination of BM wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
165
3
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 530 publications
(171 citation statements)
references
References 32 publications
2
165
3
1
Order By: Relevance
“…These results mirror the concepts pioneered by the Perugia transplant team, i.e. that a high stem cell dose can permit engraftment across major HLA barriers (Aversa et al, 1994;Reisner & Martelli, 1995), even in the presence of profound T-cell depletion for GVHD prevention. In these studies the target cell dose was between 5 × 10 6 and 10 × 10 6 CD34 þ cells/kg, which was achieved with a combination of PBPC and BM cells.…”
Section: Clinical Results Of Pbpc Transplantssupporting
confidence: 76%
See 1 more Smart Citation
“…These results mirror the concepts pioneered by the Perugia transplant team, i.e. that a high stem cell dose can permit engraftment across major HLA barriers (Aversa et al, 1994;Reisner & Martelli, 1995), even in the presence of profound T-cell depletion for GVHD prevention. In these studies the target cell dose was between 5 × 10 6 and 10 × 10 6 CD34 þ cells/kg, which was achieved with a combination of PBPC and BM cells.…”
Section: Clinical Results Of Pbpc Transplantssupporting
confidence: 76%
“…Secondly because immune reconstitution has been observed to be significantly slower in the recipients of CD34 þ selected PBPC transplants receiving comparable numbers of CD34 þ cells but much lower numbers of T cells. In the setting of mismatched donors, unmanipulated PBPC transplants have been shown to have comparable rates of immune reconstitution as that achieved with matched sibling donors which contrasts with the results of either CD34 þ selected mismatched transplants or T-cell-depleted haploidentical transplants where immune reconstitution is significantly delayed and CMV infection post-transplant has been a major cause of mortality (Bacigalupo et al, 1997;Aversa et al, 1994). Whether the more rapid immune reconstitution associated with unmanipulated PBPC allografts offers any clinical benefit is not clear, although in a recent study by the EBMT Infectious Disease working party (Link et al, 1998) the incidence of severe CMV infection following unmanipulated PBPC transplants was found to be low, affecting just 5% of CMV-positive patients with a low incidence of death from CMV disease.…”
Section: Clinical Results Of Pbpc Transplantsmentioning
confidence: 99%
“…Intensive conditioning regimens have been developed to reduce host allograft resistance (Schwartz et al, 1987): single-dose TBI (Patterson et al, 1986), antilymphocyte globulin (ALG) (Aversa et al, 1994) and thiotepa (Terenzi et al, 1990) have all been used to reduce the number of residual clonable host T cells. Experimental data in animals (Reisner et al, 1978), and recently in man (Aversa et al, 1994), have shown that the combined use of large numbers of T-celldepleted (TCD) haemopoietic stem cells with intensive conditioning regimen can result in permanent engraftment across the major histocompatibility complex. In humans, and especially in adults, one needs to combine TCD marrow with TCD peripheral blood cells mobilized with G-CSF to obtain cell numbers required for this procedure (Aversa et al, 1994).…”
mentioning
confidence: 99%
“…This was acheived using standard preparation for matched sibling donor BMT in HLH with the addition of Campath 1G. Neither TBI nor antithymocyte globulin was required, in contrast to a previous report (Aversa et al, 1994). The data provided here do not address the question of whether T-cell depletion by both Campath 1 antibodies and Cellpro columns is necessary, and it is possible that different T-cell depletion protocols may have resulted in a similar outcome.…”
Section: Discussionmentioning
confidence: 86%
“…The stem cell inoculum was increased 7-10-fold using a combination of bone marrow and peripheral blood stem cells which were T-cell depleted by soybean agglutination and E-rosetting; patients were conditioned with a total body irradiation based regimen. This strategy lead to full engraftment in all but one patient, and although nine patients died of transplantrelated toxicity, only one died of acute graft-versus-host disease (GVHD) (Aversa et al, 1994).…”
mentioning
confidence: 99%